Method for producing aliphatic aromatic polyester
By using specific nucleating agents and alkaline inorganic compounds in the manufacturing process of aliphatic aromatic polyester, the problems of insufficient crystallization and adhesion are solved, and efficient and high-quality polyester manufacturing is achieved.
Patent Information
- Application Number
- CN202180009010.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-02-12
- Filing Date
- 2021-02-02
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2041-02-02
AI Technical Summary
In the prior art, when producing aliphatic aromatic polyesters, there are problems of insufficient crystallization and adhesion of resin pellets to each other, resulting in low process efficiency and poor quality of molded products.
By introducing a specific nucleating agent into the reaction system, the difference between its melting point and the melting point of the polyester is within the range of 0°C to 100°C, the crystallization of the polyester is promoted, and alkaline inorganic compounds are used in the esterification and polycondensation reaction to improve the reaction efficiency.
The high crystallinity aliphatic aromatic polyester manufacturing is achieved, which avoids the adhesion problem of resin pellets, improves process efficiency, and improves the mechanical properties and biodegradability of molded products.
Smart Images

Figure BDA0003743359220000131 
Figure BDA0003743359220000211 
Figure BDA0003743359220000212
Abstract
Description
Technical Field
[0001] The present invention relates to a method for producing an aliphatic aromatic polyester using an aliphatic diol component, an aliphatic dicarboxylic acid component and an aromatic dicarboxylic acid component as main raw materials. Background Art
[0002] Paper, plastic, aluminum foil and other materials are used in packaging materials for liquid, powder, and solid materials such as food, medicine, and sundries, agricultural materials, and construction materials. Among them, plastics are used in a wide range of applications as molded products such as bags and containers due to their excellent strength, water resistance, moldability, transparency, and cost.
[0003] Currently, polyethylene, polypropylene, polystyrene, polyvinyl chloride, polyethylene terephthalate, and the like are widely used plastics for bags and containers. However, molded products made of the above plastics do not undergo biodegradation or hydrolysis in the natural environment, or the degradation rate is very slow, so that they may remain in the soil when they are landfilled after use, or may damage the landscape when they are discarded. In addition, when they are incinerated, there are also problems such as the generation of harmful gases or damage to the incinerator.
[0004] As an environmentally friendly plastic to solve these problems, biodegradable resins have attracted attention. The film obtained by molding the biodegradable resin is buried in the soil after use and degraded in the soil, so it can prevent global warming and prevent soil and air pollution. Therefore, in recent years, garbage bags, shopping bags, etc. are mostly made of films made of biodegradable resins.
[0005] However, films made of these biodegradable resins are generally inferior in mechanical properties in many cases, and therefore, a large number of studies have been conducted to improve the mechanical properties while maintaining good biodegradability.
[0006] As polyesters having both biodegradability and mechanical properties and moldability, aliphatic aromatic polyesters such as polybutylene succinate terephthalate (PBST) obtained by using an aliphatic diol such as 1,4-butanediol as a diol component and a combination of an aliphatic dicarboxylic acid such as succinic acid and an aromatic dicarboxylic acid such as terephthalic acid as a dicarboxylic acid component have been proposed.
[0007] Aliphatic aromatic polyesters such as PBST are produced through an esterification step and a polycondensation step similarly to other polyesters.
[0008] Patent Document 1 discloses an aliphatic aromatic polyester containing at least an aliphatic dicarboxylic acid unit, an aromatic dicarboxylic acid unit, an aliphatic and / or alicyclic diol unit, and a structural unit having a specific amount of a trifunctional or higher ester-forming group. Specifically, in Patent Document 1, succinic acid is used as a raw material aliphatic dicarboxylic acid, terephthalic acid is used as an aromatic dicarboxylic acid, 1,4-butanediol is used as an aliphatic diol, and malic acid is used as a trifunctional or higher hydroxycarboxylic acid, and a titanium compound such as titanium tetrabutyrate or an alkaline earth metal such as magnesium acetate is used as a catalyst to produce polybutylene succinate terephthalate (PBST) through an esterification step and a polycondensation step.
[0009] Patent Document 1: Japanese Patent Application Publication No. 2008-31457
[0010] Generally, the industrial method for producing aliphatic aromatic polyesters such as PBST is as follows: a raw material aliphatic diol component, aliphatic dicarboxylic acid component and aromatic dicarboxylic acid component are continuously supplied to a reaction system in the presence of a catalyst, and a high-temperature molten polymer is continuously obtained from the reaction system through a polycondensation reaction step of esterification and / or transesterification reaction, and the obtained polymer is granulated (pelletized) while being cooled.
[0011] It has been found that when aliphatic aromatic polyesters such as PBST are produced by the method described in Patent Document 1, the obtained aliphatic aromatic polyesters are not sufficiently crystallized and the obtained aliphatic aromatic polyester resin pellets are adhered to each other. Furthermore, as a result, in order to fully ensure the crystallization time, the cooling process for cooling the polymer in a high-temperature molten state becomes longer, which may become an economically inefficient process as a process for industrially producing aliphatic aromatic polyesters such as PBST. In addition, when aliphatic aromatic polyesters such as PBST with a slow crystallization rate obtained by the method described in Patent Document 1 are used to obtain films or bags formed by inflation molding, there is a concern that the films cannot be cut due to welding, or the bag obtained by inflation molding has an insufficient opening. Summary of the invention
[0012] The present invention aims to solve the above-mentioned problems of the prior art and to provide a method for producing aliphatic aromatic polyesters with high crystallinity by improving the existing insufficient crystallinity when producing aliphatic aromatic polyesters such as PBST by esterification and / or transesterification reaction and polycondensation reaction.
[0013] The present inventors have found that when aliphatic aromatic polyesters such as PBST are produced by esterification and / or transesterification and polycondensation, insufficient crystallization can be improved and the above-mentioned problems can be solved by allowing a specific nucleating agent to exist in the reaction system, thereby completing the present invention.
[0014] The gist of the present invention lies in the following [1] to [9].
[0015] [1] A method for producing an aliphatic aromatic polyester, characterized in that when an aliphatic diol component, an aliphatic dicarboxylic acid component and an aromatic dicarboxylic acid component as raw materials are subjected to an esterification and / or ester exchange reaction and a polycondensation reaction in the presence of a catalyst to produce the aliphatic aromatic polyester, a nucleating agent satisfying the conditions of the following formula (1) is allowed to exist in the reaction system.
[0016] 0℃ <Tm 1 -Tm 2 ≤100℃···(1)
[0017] (In the above formula (1), Tm 1 : Melting point of nucleating agent (℃), Tm 2 : Melting point of aliphatic aromatic polyester (℃)
[0018] [2] The method for producing an aliphatic aromatic polyester according to [1], wherein the nucleating agent is present in an amount of 100 to 10,000 ppm by weight based on the produced aliphatic aromatic polyester.
[0019] [3] The method for producing an aliphatic aromatic polyester according to [1] or [2], wherein the molar ratio of the aliphatic dicarboxylic acid component to the aromatic dicarboxylic acid component is 40:60 to 60:40.
[0020] [4] The method for producing an aliphatic aromatic polyester according to any one of [1] to [3], wherein the esterification and / or transesterification reaction is carried out in the presence of a basic inorganic compound.
[0021] [5] The method for producing an aliphatic aromatic polyester according to [4], wherein the basic inorganic compound is present in an amount of 1 to 100 ppm by weight in terms of metal atoms relative to the produced aliphatic aromatic polyester.
[0022] [6] The method for producing an aliphatic aromatic polyester according to any one of [1] to [5], wherein the aliphatic dicarboxylic acid component is a succinic acid component.
[0023] [7] The method for producing an aliphatic aromatic polyester according to any one of [1] to [6], wherein the aromatic dicarboxylic acid component is a terephthalic acid component and / or a furan dicarboxylic acid component.
[0024] [8] The method for producing an aliphatic aromatic polyester according to any one of [1] to [7], wherein the aliphatic dicarboxylic acid component is a component derived from biomass.
[0025] [9] The method for producing an aliphatic aromatic polyester according to any one of [1] to [8], wherein the aliphatic diol component is a component derived from biomass.
[0026] Effects of the Invention
[0027] According to the present invention, when an aliphatic aromatic polyester such as PBST is produced by esterification and / or transesterification reaction and polycondensation reaction, by allowing a specific nucleating agent to exist in the reaction system, an aliphatic aromatic polyester that can improve the problem of insufficient crystallization and does not cause the problem of adhesion between resin pellets or fusion between films can be produced industrially and advantageously. In addition, it is expected that a high-quality molded product can be provided using the aliphatic aromatic polyester. DETAILED DESCRIPTION
[0028] The following description of the components is an example (representative example) of the embodiment of the present invention, and the present invention is not limited to these contents unless it exceeds the gist thereof.
[0029] In the present specification, "mass %", "mass ppm" and "mass parts" have the same meanings as "weight %", "weight ppm" and "weight parts", respectively.
[0030] The method for producing an aliphatic aromatic polyester of the present invention is characterized in that when an aliphatic diol component, an aliphatic dicarboxylic acid component and an aromatic dicarboxylic acid component as raw materials are subjected to an esterification and / or ester exchange reaction and a polycondensation reaction in the presence of a catalyst to produce an aliphatic aromatic polyester, a nucleating agent satisfying the conditions of the following formula (1) is allowed to exist in the reaction system.
[0031] 0℃ <Tm 1 -Tm 2 ≤100℃···(1)
[0032] (In the above formula (1), Tm 1 : Melting point of nucleating agent (℃), Tm 2 : Melting point of aliphatic aromatic polyester (℃)
[0033] Here, the term "aliphatic dicarboxylic acid component" is a general term for aliphatic dicarboxylic acids such as aliphatic dicarboxylic acids and aliphatic dicarboxylic acid derivatives such as aliphatic dicarboxylic acid alkyl esters, which are raw materials for polyesters. The term "aromatic dicarboxylic acid component" is a general term for aromatic dicarboxylic acids such as aromatic dicarboxylic acids and aromatic dicarboxylic acid derivatives such as aromatic dicarboxylic acid alkyl esters, which are raw materials for polyesters.
[0034] In the present invention, the "aromatic dicarboxylic acid" is an "aromatic dicarboxylic acid" in a broad sense including a "heteroaromatic dicarboxylic acid".
[0035] Hereinafter, the aliphatic aromatic polyester produced by the method for producing an aliphatic aromatic polyester of the present invention may be referred to as “the aliphatic aromatic polyester of the present invention.” In addition, the aliphatic aromatic polyester may be simply referred to as “polyester.”
[0036] The production method of the present invention comprises at least: an esterification and / or transesterification reaction step in which an aliphatic diol component, an aliphatic dicarboxylic acid component and an aromatic dicarboxylic acid component are reacted as main raw materials in the presence of a catalyst, and a subsequent polycondensation reaction step. "Using an aliphatic diol component, an aliphatic dicarboxylic acid component and an aromatic dicarboxylic acid component as main raw materials" means that the diol component used as a raw material mainly contains an aliphatic diol component, and the dicarboxylic acid component used as a raw material mainly contains an aliphatic dicarboxylic acid component and an aromatic dicarboxylic acid component.
[0037] Here, "having aliphatic diol components as the main component" means "the total molar ratio of aliphatic diol components is the largest in the raw material diol components". However, from the aspects of the physical properties and biodegradability of the obtained polyester, the total amount of aliphatic diol components is preferably 50 mol% or more, more preferably 60 mol% or more, further preferably 70 mol% or more, and particularly preferably 90 to 100 mol% relative to the total amount of raw material diol components.
[0038] In addition, “containing aliphatic dicarboxylic acid and aromatic dicarboxylic acid as main components” means “the total molar ratio of the aliphatic dicarboxylic acid component and the aromatic dicarboxylic acid component is the largest in the raw material carboxylic acid component”. In particular, from the perspective of the physical properties and biodegradability of the obtained polyester, the total molar ratio of the aliphatic dicarboxylic acid component and the aromatic dicarboxylic acid component is preferably 50 mol% or more, more preferably 60 mol% or more, further preferably 70 mol% or more, and particularly preferably 90 to 100 mol% relative to the total molar ratio of the raw material carboxylic acid component.
[0039] In the present invention, each reaction step in producing polyester may be carried out by a batch method or a continuous method. From the viewpoint of stabilizing quality and energy efficiency, a so-called continuous method in which raw materials are continuously supplied and polyester is continuously obtained is preferred.
[0040] <Nucleating agent>
[0041] The nucleating agent used in the method for producing an aliphatic aromatic polyester of the present invention is characterized in that the melting point (Tm) of the produced aliphatic aromatic polyester is 2 (℃)) and the melting point of the nucleating agent (Tm 1 (℃)) difference (Tm1 -Tm 2 ) is in the range of 0 to 100°C. By using a nucleating agent that satisfies such a melting point condition, the crystallization exothermic peak time (the cooling crystallization peak time described later) of the molten aliphatic aromatic polyester obtained by the polycondensation reaction during cooling can be shortened, so that the crystallization of the aliphatic aromatic polyester is promoted during cooling. As a result, the cooling process can be shortened, so pellets of the aliphatic aromatic polyester can be continuously produced economically and efficiently.
[0042] Melting point Tm of nucleating agent 1 The measuring method of is not particularly limited, and it can be measured, for example, by a visual method (JIS K6220), a thermal analysis method based on DCS or DTA, etc. If it is a commercially available product, the catalog value can be used.
[0043] Melting point (Tm) of aliphatic aromatic polyester 2 The method for measuring the melting point of the aliphatic aromatic polyester of the present invention is also not particularly limited, and the melting point can be measured, for example, by the method described in the subsequent examples. The appropriate melting point of the aliphatic aromatic polyester of the present invention is described below.
[0044] In the present invention, the melting point (Tm 2 (℃)) and the melting point of the nucleating agent (Tm 1 (℃)) difference (Tm 1 -Tm 2 ) is 100°C or lower, preferably 50°C or lower, more preferably 40°C or lower, further preferably 20°C or lower, and most preferably 15°C or lower. 1 -Tm 2 The smaller the value of Tm, the shorter the crystallization exothermic peak time. However, in order for the nucleating agent to function as a crystallization nucleus, it is necessary to cure faster than the aliphatic aromatic polyester. 1 -Tm 2 It is 0°C or higher, preferably 1°C or higher, and more preferably 3°C or higher.
[0045] The type of nucleating agent is not particularly limited as long as it satisfies the above conditions. As the nucleating agent, for example, hydrocarbon nucleating agents such as polyethylene wax and polypropylene wax, aliphatic amide nucleating agents, phosphate metal salt nucleating agents, etc. can be used. From the perspective of the color tone of the obtained aliphatic aromatic polyester and the influence on the polymerizability, hydrocarbon nucleating agents are preferred, polyethylene wax and polypropylene wax are more preferred, and polyethylene wax is further preferred.
[0046] Regarding polyethylene wax and polypropylene wax, commercial products having various melting points depending on the molecular weight, the presence or absence of branching, the copolymer component composition, etc., and a commercial product satisfying the above melting point conditions can be selected and used from the commercial products.
[0047] As long as the above-mentioned melting point conditions are satisfied, only one type of nucleating agent may be used, or two or more types may be used in combination.
[0048] In the method for producing aliphatic aromatic polyesters of the present invention, there is no particular limitation on the method for making a nucleating agent exist in the reaction system. The nucleating agent may be present in the esterification and / or transesterification reaction system, or in the polycondensation reaction system. For example, there are the following methods: a method of supplying the nucleating agent to the reaction tank of the esterification and / or transesterification reaction together with the aliphatic diol component, aliphatic dicarboxylic acid component, and aromatic dicarboxylic acid component as raw materials described later; a method of adding the nucleating agent directly to the reaction tank of the esterification and / or transesterification reaction separately from these raw materials; a method of adding the nucleating agent to the polycondensation reaction tank; a method of adding the nucleating agent to the extruder that is attached to the polycondensation reaction tank and transfers the polyester in a high-temperature molten state to the next step; and the like. Two or more of these methods may also be used in combination.
[0049] In the method for producing aliphatic aromatic polyesters of the present invention, the amount of the nucleating agent present in the reaction system is preferably 100 to 10,000 ppm by weight relative to the generated aliphatic aromatic polyester. The amount of the nucleating agent is more preferably 200 to 5,000 ppm by weight, and further preferably 500 to 3,000 ppm by weight. When the amount of the nucleating agent is below the upper limit, the amount of the nucleating agent distilled from the reaction system can be suppressed, and the situation in which the overall process load is increased due to the inability to recover the nucleating agent by the subsequent distillation or distillation system can be prevented. When the amount of the nucleating agent is above the lower limit, the crystallization of the obtained aliphatic aromatic polyester can be fully carried out.
[0050] <Diol component>
[0051] As the diol component used in the present invention, as described above, at least an aliphatic diol component is used and the total molar ratio thereof is the largest among the raw material diol components, and any diol component generally used as a raw material for polyester can be used without particular limitation.
[0052] Examples of the aliphatic diol component include alkylene glycols such as ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 1,4-butylene glycol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol and neopentyl glycol; oxyalkylene glycols such as diethylene glycol, polyethylene glycol, polypropylene glycol and polytetramethylene ether glycol; and cycloalkylene glycols such as 1,2-cyclohexanediol, 1,4-cyclohexanediol, 1,2-cyclohexanedimethanol and 1,4-cyclohexanedimethanol. Among these, alkylene glycols having 6 or less carbon atoms such as ethylene glycol, 1,3-propylene glycol, and 1,4-butanediol, or cycloalkylene glycols having 6 or less carbon atoms such as 1,4-cyclohexanedimethanol are preferred from the viewpoint of the physical properties of the obtained polyester, and 1,4-butanediol is particularly preferred. Two or more of these may be used in combination.
[0053] When 1,4-butanediol is used as the aliphatic diol component, the amount of 1,4-butanediol used is preferably 50 mol% or more, more preferably 70 mol% or more, particularly preferably 90 to 100 mol% based on the total aliphatic diol components, from the viewpoints of the melting point (heat resistance), biodegradability and mechanical properties of the obtained polyester.
[0054] Among the aliphatic diol components, ethylene glycol, 1,3-propylene glycol, and 1,4-butanediol are preferably those derived from biomass (plant raw materials).
[0055] <Dicarboxylic acid component>
[0056] As the carboxylic acid component used in the present invention, as described above, at least an aliphatic dicarboxylic acid component and an aromatic dicarboxylic acid component are used and their total molar ratio is the largest among the raw material dicarboxylic acid components, and dicarboxylic acid components generally used as raw materials for polyester can be used without particular limitation.
[0057] Among the dicarboxylic acid components, as the aliphatic dicarboxylic acid component, for example, aliphatic dicarboxylic acids such as oxalic acid, malonic acid, succinic acid, succinic anhydride, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, undecanedicarboxylic acid, dodecanedicarboxylic acid, dimer acid, and the like, and hydrogenated products of aromatic dicarboxylic acids such as hexahydrophthalic acid, hexahydroisophthalic acid, and hexahydroterephthalic acid can be cited. Among these, aliphatic dicarboxylic acids such as succinic acid, succinic anhydride, adipic acid, and sebacic acid, or derivatives thereof such as alkyl esters are preferred from the aspect of the physical properties of the obtained polyester. In particular, succinic acid is preferred because of the significant effect of improving crystallization brought about by the present invention. Two or more of them may also be used in combination.
[0058] Among these aliphatic dicarboxylic acid components, succinic acid, succinic anhydride, adipic acid and the like are preferably those derived from biomass (plant raw materials).
[0059] When succinic acid is used as the aliphatic dicarboxylic acid component, the amount of succinic acid used is preferably 50 mol% or more, more preferably 70 mol% or more, particularly preferably 90 to 100 mol% based on the total aliphatic dicarboxylic acid components, from the viewpoints of the melting point (heat resistance), biodegradability and mechanical properties of the obtained polyester.
[0060] As the aromatic dicarboxylic acid component, for example, terephthalic acid, isophthalic acid, naphthalene dicarboxylic acid, diphenyl dicarboxylic acid, furandicarboxylic acid, or derivatives thereof such as alkyl esters, etc. are mentioned. From the viewpoint of the physical properties of the obtained polyester, terephthalic acid, isophthalic acid, and furandicarboxylic acid are preferred, and terephthalic acid and furandicarboxylic acid are particularly preferred. These components may be used alone or as a mixture of two or more thereof.
[0061] When terephthalic acid is used as the aromatic dicarboxylic acid component, the amount of terephthalic acid used is preferably 50 mol% or more, more preferably 70 mol% or more, particularly preferably 90 to 100 mol% based on the total aromatic dicarboxylic acid components, from the viewpoint of the melting point (heat resistance) and mechanical properties of the obtained polyester.
[0062] In addition, the molar ratio of the aliphatic dicarboxylic acid component to the aromatic dicarboxylic acid component used in the present invention is preferably aliphatic dicarboxylic acid component:aromatic dicarboxylic acid component = 40:60 to 60:40, and particularly preferably aliphatic dicarboxylic acid component:aromatic dicarboxylic acid component = 50:50 to 60:40 from the perspectives of heat resistance, biodegradability, mechanical properties and moldability of the obtained polyester.
[0063] In the method for producing aliphatic aromatic polyesters of the present invention, the aliphatic aromatic polyester produced is not particularly limited as long as it is a product obtained by combining the above-mentioned aliphatic diol component, aliphatic dicarboxylic acid component and aromatic dicarboxylic acid component, but is preferably polybutylene succinate terephthalate (PBST) or polybutylene succinate furanoate (PBSF).
[0064] <Other copolymer components>
[0065] The aliphatic aromatic polyester of the present invention may be copolymerized with other components other than the aliphatic diol component, the aliphatic dicarboxylic acid component, and the aromatic dicarboxylic acid component. Examples of copolymerization components that can be used in this case include hydroxycarboxylic acids such as lactic acid, glycolic acid, hydroxybutyric acid, hydroxycaproic acid, 2-hydroxy-3,3-dimethylbutyric acid, 2-hydroxy-3-methylbutyric acid, 2-hydroxyisocaproic acid, malic acid, maleic acid, citric acid, and fumaric acid, and esters or lactones of these hydroxycarboxylic acids, hydroxycarboxylic acid polymers, or trifunctional or higher polyols such as glycerol, trimethylolpropane, and pentaerythritol, or trifunctional or higher polycarboxylic acids such as propanetricarboxylic acid, pyromellitic acid, trimellitic acid, benzophenonetetracarboxylic acid, and their anhydrides, or their anhydrides.
[0066] Among these, polyester with high viscosity can be easily obtained by adding a small amount of trifunctional or higher hydroxycarboxylic acid, trifunctional or higher alcohol, trifunctional or higher carboxylic acid, etc. Among them, hydroxycarboxylic acids such as malic acid, citric acid, and fumaric acid, or polyols such as glycerol, trimethylolpropane, and pentaerythritol are preferred, and trimethylolpropane is particularly preferred.
[0067] When a trifunctional or higher polyfunctional compound is used, the amount thereof is preferably 0.001 to 5 mol%, more preferably 0.05 to 0.5 mol%, relative to the total dicarboxylic acid components. When the amount of the trifunctional or higher polyfunctional compound is below the upper limit, it is easy to suppress the formation of gel (unmelted material) in the obtained polyester. When the amount of the trifunctional or higher polyfunctional compound is above the lower limit, it is easy to obtain the advantages brought by the use of the polyfunctional compound (usually the viscosity of the obtained polyester can be increased).
[0068] <Basic Inorganic Compounds>
[0069] In the method for producing aliphatic aromatic polyesters of the present invention, it is preferred that a basic inorganic compound be present in the esterification and / or transesterification reaction step. By allowing a basic inorganic compound to be present in the esterification and / or transesterification reaction step, the amount of tetrahydrofuran in the obtained aliphatic aromatic polyester can be reduced, and the terminal acid value can be reduced.
[0070] Examples of the alkaline inorganic compound include alkali metal hydroxides such as sodium hydroxide, potassium hydroxide, and lithium hydroxide, and sodium hydroxide is preferred. These compounds may be used alone or as a mixture of two or more.
[0071] The amount of the basic inorganic compound used is preferably 1 to 100 ppm by weight, more preferably 1 to 50 ppm by weight, based on the metal atomic weight relative to the obtained aliphatic aromatic polyester. When the amount of the basic inorganic compound is greater than or equal to the above lower limit, the above effect brought about by the basic inorganic compound can be fully obtained. When the amount of the basic inorganic compound is less than or equal to the above upper limit, the decrease in polymerization activity and the generation of foreign matter due to the reaction with the dicarboxylic acid component can be suppressed.
[0072] The basic inorganic compound can be added in the esterification and / or transesterification reaction step as long as it is present in the esterification and / or transesterification reaction step, or in a step before the esterification and / or transesterification reaction step. For example, the basic inorganic compound can be supplied to the esterification and / or transesterification reaction tank together with the aliphatic diol component, aliphatic dicarboxylic acid component, aromatic dicarboxylic acid component, etc. as raw materials, or can be directly supplied to the reaction tank separately from these raw materials.
[0073] <Method for producing aliphatic aromatic polyester>
[0074] The method for producing the aliphatic aromatic polyester of the present invention will be described below by taking a continuous production method as an example.
[0075] The following is an example of a method for producing an aliphatic aromatic polyester by an esterification reaction step using an aliphatic diol, an aliphatic dicarboxylic acid and an aromatic dicarboxylic acid and a subsequent polycondensation reaction step, but the esterification reaction step may be an ester exchange reaction step or a step of performing both esterification and ester exchange reactions.
[0076] In the continuous production method, for example, two or more continuous reaction tanks are used to continuously obtain polyester pellets by subjecting aliphatic dicarboxylic acids and aromatic dicarboxylic acids to an esterification reaction step and a melt polycondensation reaction step. The method is not limited to the continuous method, and a conventionally known method for producing aliphatic aromatic polyesters may be used as long as the effect of the present invention is not impaired.
[0077] The esterification reaction step of reacting at least a dicarboxylic acid component with a diol component and the subsequent polycondensation reaction step may be carried out using two or more continuous reaction tanks or a single reaction tank. In order to reduce the variation in the physical properties of the obtained polyester, it is preferably carried out using two or more continuous reaction tanks.
[0078] The description of the supply of nucleating agent and the supply of basic inorganic compound is omitted below, but in the present invention, as described above, a specific nucleating agent is supplied in the esterification and / or ester exchange reaction process and the polycondensation reaction process, and preferably a basic inorganic compound is supplied in the esterification and / or ester exchange reaction process.
[0079] <Esterification reaction step>
[0080] The reaction temperature in the esterification reaction step is not particularly limited as long as it is a temperature at which the esterification reaction can proceed. From the perspective of being able to increase the reaction rate, it is preferably 200°C or higher, more preferably 210°C or higher. On the other hand, in order to prevent the coloring of the polyester, the reaction temperature is preferably 270°C or lower, more preferably 260°C or lower, and particularly preferably 250°C or lower. If the reaction temperature is too low, the esterification reaction rate slows down, and the reaction time needs to be extended, and unfavorable reactions such as dehydration and decomposition of aliphatic diols increase. If the reaction temperature is too high, the decomposition amount of aliphatic diols, aliphatic dicarboxylic acids, and aromatic dicarboxylic acids increases, and the amount of scattered matter in the reaction tank increases, which is likely to cause the generation of foreign matter, and turbidity (haze) is likely to occur in the reactants.
[0081] The esterification reaction temperature is preferably a constant temperature. By keeping the temperature constant, the esterification rate is stabilized. The constant temperature is ±5°C of the set temperature, preferably ±2°C.
[0082] The reaction atmosphere is preferably an inert gas atmosphere such as nitrogen or argon.
[0083] The reaction pressure is preferably 50 kPa to 200 kPa, more preferably 60 kPa or more, further preferably 70 kPa or more, more preferably 130 kPa or less, further preferably 110 kPa or less. When the reaction pressure is less than the above lower limit, the amount of scattered matter in the reaction tank increases, the mist of the reactants increases, and it is easy to become a cause of increased foreign matter, and the distillation of aliphatic diols outside the reaction system increases, which is easy to cause a decrease in the polycondensation reaction rate. If the reaction pressure exceeds the above upper limit, the dehydration and decomposition of aliphatic diols increases, which is easy to cause a decrease in the polycondensation reaction rate.
[0084] The reaction time is preferably 1 hour or longer, and the upper limit is preferably 10 hours or shorter, more preferably 4 hours or shorter.
[0085] The reaction molar ratio of the aliphatic diol relative to the total of the aliphatic dicarboxylic acid and the aromatic dicarboxylic acid for the esterification reaction represents the molar ratio of the aliphatic diol and the esterified aliphatic diol relative to the aliphatic dicarboxylic acid and the aromatic dicarboxylic acid present in the gas phase and the reaction liquid phase of the esterification reaction tank, and the aliphatic dicarboxylic acid and the aromatic dicarboxylic acid esterified, and does not include the aliphatic dicarboxylic acid, the aromatic dicarboxylic acid, the aliphatic diol and their decomposition products that decompose in the reaction system and do not contribute to the esterification reaction. For example, 1,4-butanediol as an aliphatic diol decomposes to become tetrahydrofuran, and tetrahydrofuran is not included in the molar ratio. In the present invention, the lower limit of the above reaction molar ratio is usually 1.10 or more, preferably 1.12 or more, more preferably 1.15 or more, and particularly preferably 1.20 or more. The upper limit of the above reaction molar ratio is usually 3.00 or less, preferably 2.50 or less, more preferably 2.30 or less, and particularly preferably 2.00 or less. If the reaction molar ratio is less than the above lower limit, the esterification reaction is likely to be insufficient, and it is difficult to carry out the polycondensation reaction as the reaction of the subsequent step, and it is difficult to obtain a polyester with a high degree of polymerization. If the reaction molar ratio exceeds the above upper limit, the decomposition amount of the aliphatic diol, aliphatic dicarboxylic acid, and aromatic dicarboxylic acid tends to increase. In order to ensure that the reaction molar ratio is within the preferred range, it is a preferred method to appropriately supplement the aliphatic diol in the esterification reaction system.
[0086] <Polycondensation Reaction Step>
[0087] In the method for producing aliphatic aromatic polyesters of the present invention, a polycondensation reaction is carried out in a polycondensation reaction step after the esterification reaction step.
[0088] The polycondensation reaction can be carried out under reduced pressure using two or more consecutive reaction tanks.
[0089] Regarding the reaction pressure of the final polycondensation reaction tank in the polycondensation reaction process, the lower limit is usually 0.01 kPa or more, preferably 0.03 kPa or more, and the upper limit is usually 1.4 kPa or less, preferably 0.4 kPa or less. If the pressure during the polycondensation reaction is too high, the polycondensation time becomes long, and the molecular weight decreases or coloring occurs due to the thermal decomposition of the polyester associated therewith, and there is a tendency that it is difficult to produce polyester that exhibits sufficient characteristics in practical use. From the aspect of increasing the polycondensation reaction speed, a method of using an ultra-high vacuum polycondensation device that makes the reaction pressure less than 0.01 kPa for production is a preferred method, but it requires a very high amount of equipment investment, so it is economically disadvantageous.
[0090] The lower limit of the reaction temperature is usually 215° C., preferably 220° C., and the upper limit is usually 270° C., preferably 260° C. If the reaction temperature is lower than the lower limit, the polycondensation reaction rate becomes slow, and the production of a polyester with a high degree of polymerization requires not only a long time but also a high-powered stirrer, which is economically disadvantageous. If the reaction temperature exceeds the upper limit, thermal decomposition of the polyester during production is likely to occur, and there is a tendency that it is difficult to produce a polyester with a high degree of polymerization.
[0091] The lower limit of the reaction time is usually 1 hour, and the upper limit is usually 15 hours, preferably 10 hours, and more preferably 8 hours. If the reaction time is too short, the reaction is insufficient, and it is difficult to obtain a polyester with a high degree of polymerization, and the mechanical properties of the molded article tend to deteriorate. If the reaction time is too long, the molecular weight reduction due to thermal decomposition of the polyester becomes significant, and not only the mechanical properties of the molded article tend to deteriorate, but also the amount of carboxyl terminals that adversely affects the durability of the polyester may increase due to thermal decomposition.
[0092] By controlling the polycondensation reaction temperature, time and reaction pressure, a polyester having a desired intrinsic viscosity can be obtained.
[0093] <Reaction Catalyst>
[0094] In the esterification reaction and the polycondensation reaction, the reaction can be accelerated by using a reaction catalyst. When a catalyst is used, when the catalyst is added to the gas phase portion of the reaction tank, the haze of the obtained polyester may increase, and the catalyst may become a foreign matter. Therefore, it is preferred to add the catalyst to the reaction solution.
[0095] In the polycondensation reaction, the reaction is difficult to proceed without a catalyst, so it is preferred to use a catalyst. The polycondensation reaction catalyst can be added at any stage from the esterification reaction step to the polycondensation reaction step. The polycondensation reaction catalyst can be added in multiple times between the esterification reaction step and the polycondensation reaction step.
[0096] As a polycondensation catalyst, a compound containing at least one metal element of Groups 1 to 14 of the periodic table is generally used. As the metal element, specifically, there can be mentioned scandium, yttrium, samarium, titanium, zirconium, vanadium, chromium, molybdenum, tungsten, tin, antimony, cerium, germanium, zinc, cobalt, manganese, iron, aluminum, magnesium, calcium, strontium, sodium and potassium. Among them, scandium, yttrium, titanium, zirconium, vanadium, molybdenum, tungsten, zinc, iron and germanium are preferred, and titanium, zirconium, tungsten, iron and germanium are particularly preferred. Furthermore, in order to reduce the polyester terminal concentration that affects the thermal stability of the polyester, among the above metals, metal elements of Groups 3 to 6 of the periodic table showing Lewis acidity are preferred. Specifically, scandium, titanium, zirconium, vanadium, molybdenum and tungsten are preferred, and titanium and zirconium are preferred from the aspect of easy availability, and titanium is preferred from the aspect of reactivity.
[0097] Here, the periodic table refers to the long-period periodic table (Nomenclature of Inorganic Chemistry IUPAC Recommendations 2005).
[0098] In the present invention, it is preferred to use a titanium compound as a catalyst in the esterification reaction step.
[0099] As the titanium compound, tetraalkyl titanate and its hydrolyzate are preferred, and specifically, tetra-n-propyl titanate, tetra-isopropyl titanate, tetra-n-butyl titanate, tetra-tert-butyl titanate, tetraphenyl titanate, tetracyclohexyl titanate, tetrabenzyl titanate, mixed titanates thereof, and their hydrolyzates are exemplified.
[0100] In addition, titanium acetylacetonate, titanium tetraacetylacetonate, (diisopropoxy)titanium acetylacetonate, di(2-hydroxypropionic acid)diammonium dihydroxide titanium, diisopropyl bis(ethyl acetylacetate), (triethanolamine)titanium isopropoxide, polyhydroxystearate titanium, titanium lactate, triethanolamine titanium, and butyl titanate dimer can also be used.
[0101] Among these, tetra-n-propyl titanate, tetraisopropyl titanate, tetra-n-butyl titanate, acetylacetonato titanium, tetraacetylacetonato titanium, di(2-hydroxypropionic acid) diammonium dihydroxide titanium, polyhydroxy titanium stearate, titanium lactate, and butyl titanate dimer are preferred; tetra-n-butyl titanate, acetylacetonato titanium, tetraacetylacetonato titanium, polyhydroxy titanium stearate, titanium lactate, and butyl titanate dimer are more preferred; and tetra-n-butyl titanate, polyhydroxy titanium stearate, acetylacetonato titanium, and tetraacetylacetonato titanium are particularly preferred.
[0102] These titanium compounds are supplied to the esterification reaction process in the form of a catalyst solution, which is prepared using a catalyst dissolving solvent such as alcohols such as methanol, ethanol, isopropanol, butanol, glycols such as ethylene glycol, butanediol, pentanediol, ethers such as diethyl ether, tetrahydrofuran, nitriles such as acetonitrile, hydrocarbon compounds such as heptane, toluene, water, and mixtures thereof, so that the titanium compound concentration is generally 0.05 to 5% by weight.
[0103] <Phosphorus compounds>
[0104] In the production of aliphatic aromatic polyesters, especially when adipic acid is used as an aliphatic dicarboxylic acid component, the obtained aliphatic aromatic polyester is colored red to pink. The molded product obtained by molding the colored aliphatic aromatic polyester is red, which may cause the problem of quality deterioration. In addition, 1,4-butanediol used as a raw material diol component has high decomposability and is prone to by-product tetrahydrofuran, which may cause problems such as low efficiency (deterioration of 1,4-butanediol unit consumption, etc.).
[0105] The gas distilled from the esterification and / or transesterification reaction tank and the polycondensation reaction tank includes aliphatic diol components and water as by-products as main components, for example, when 1,4-butanediol is used as the aliphatic diol component, tetrahydrofuran as its decomposition product is also included. These gas components are usually separated and captured by a distillation tower, a wet condenser, etc., and the high boiling components mainly composed of the raw material diol component are sometimes reused as part of the raw material. However, since tetrahydrofuran does not contribute to the ester reaction, if the by-product of tetrahydrofuran is large, the unit consumption of 1,4-butanediol will be deteriorated, which is not preferred.
[0106] As a measure to solve this problem and to produce high-quality aliphatic aromatic polyesters with suppressed by-production of tetrahydrofuran and good color tone, the following method is effective: the terminal acid value of an ester oligomer obtained by an esterification and / or transesterification reaction step in which an aliphatic diol component, an aliphatic dicarboxylic acid component and an aromatic dicarboxylic acid component are reacted is controlled to be 30 to 1000 eq. / ton, and a phosphorus compound is brought into contact with the ester oligomer with the controlled terminal acid value to carry out a polycondensation reaction.
[0107] In this case, examples of the phosphorus compound to be contacted with the ester oligomer having a terminal acid value of 30 to 1000 eq. / ton obtained in the esterification and / or transesterification reaction step include orthophosphoric acid, polyphosphoric acid, and pentavalent phosphorus compounds such as trimethyl phosphate, triethyl phosphate, tri-n-butyl phosphate, trioctyl phosphate, triphenyl phosphate, tricresyl phosphate, tri(triethylene glycol) phosphate, diethylphosphonoethyl acetate, methyl acid phosphate, ethyl acid phosphate, isopropyl acid phosphate, butyl acid phosphate, monobutyl phosphate, dibutyl phosphate, dioctyl phosphate, and triethylene glycol acid phosphate, and trivalent phosphorus compounds such as phosphorous acid, hypophosphorous acid, diethyl phosphite, tridodecyl phosphite, tri(nonyldecyl) phosphite, and triphenyl phosphite. Among these, acidic phosphoric acid ester compounds are preferred. As the acidic phosphate compound, a compound having a phosphate structure (the structure having at least one hydroxyl group) represented by the following general formula (I) and / or (II) is preferably used.
[0108] [Chemistry 1]
[0109]
[0110] In the formula, R, R', and R" each represent an alkyl group having 1 to 6 carbon atoms, a cyclohexyl group, an aryl group, or a 2-hydroxyethyl group. In formula (I), R and R' may be the same or different.
[0111] Specific examples of such acidic phosphate compounds include methyl acid phosphate, ethyl acid phosphate, isopropyl acid phosphate, butyl acid phosphate, octyl acid phosphate, etc., preferably ethyl acid phosphate and butyl acid phosphate. These acidic phosphate compounds may be used alone or in combination of two or more.
[0112] The acidic phosphate compound contains a monoester represented by the general formula (II) and a diester represented by the general formula (I). For the reason of obtaining a catalyst showing high catalytic activity, it is preferred to use a monoester or a mixture of a monoester and a diester. The mixing weight ratio of the monoester to the diester (monoester: diester) is preferably 80 or less: 20 or more, more preferably 70 or less: 30 or more, particularly preferably 60 or less: 40 or more, preferably 20 or more: 80 or less, more preferably 30 or more: 70 or less, and particularly preferably 40 or more: 60 or less.
[0113] In the method using a phosphorus compound as described above, it is preferred to contact an alkaline earth metal compound with the phosphorus compound together with the ester oligomer. In this case, various compounds of beryllium, magnesium, calcium, strontium, barium, etc. can be cited as alkaline earth metal compounds. From the perspective of ease of handling or obtaining and catalytic effect, magnesium and calcium compounds are preferred, and magnesium compounds with excellent catalytic effect are preferred. Specific examples of magnesium compounds include magnesium acetate, magnesium hydroxide, magnesium carbonate, magnesium oxide, magnesium alkoxide, magnesium hydrogen phosphate, etc. Among these, magnesium acetate is preferred.
[0114] These phosphorus compounds and alkaline earth metal compounds are preferably added to the ester oligomer supplied to the polycondensation reaction step in the form of a catalyst solution prepared in such a manner that the phosphorus compound is 0.01 to 7.6% by weight and the alkaline earth metal compound is 0.02 to 9.7% by weight using the solvent exemplified as the catalyst dissolving solvent used in the preparation of the catalyst solution of the titanium compound.
[0115] There is no particular restriction on the amount and ratio of the titanium compound used in the esterification reaction step and the phosphorus compound and alkaline earth metal compound used in the polycondensation reaction step. For example, the titanium compound is preferably used in an amount of 5 to 100 ppm by weight calculated as Ti conversion relative to the generated polyester. The phosphorus compound is preferably used in an amount of 0.5 to 2.5 in terms of the ratio of the added mole of P conversion relative to the added mole of Ti conversion of the titanium compound (P / Ti molar ratio). The alkaline earth metal compound is preferably used in an amount of 0.5 to 3.0 in terms of the ratio of the added mole of alkaline earth metal conversion relative to the added mole of Ti conversion of the titanium compound (alkaline earth metal / Ti molar ratio). If any of the catalyst compounds is too much, it is not only economically disadvantageous, but also the terminal acid value in the polyester finally obtained may increase (although the reason is still unclear), so the thermal stability and hydrolysis resistance of the polyester may be reduced due to the increase in the terminal acid value and the residual catalyst concentration. On the contrary, if the catalyst compound is too little, the reaction activity is reduced, and the thermal decomposition of the polyester will be induced in the polyester production, and it is difficult to obtain a polyester showing practically useful properties.
[0116] <Reaction tank>
[0117] As the esterification reaction tank used in the present invention, a known reaction tank can be used, and any type such as a vertical stirring complete mixing tank, a vertical heat convection mixing tank, a tower type continuous reaction tank, etc. can be cited. In addition, the reaction tank can be a single tank, or a plurality of tanks of the same or different types connected in series. Among them, a reaction tank with a stirring device is preferred. As the stirring device, in addition to the usual type consisting of a power unit and a bearing, a shaft, and a stirring paddle, a high-speed rotating type such as a turbine stator type high-speed rotating mixer, a disc mill type mixer, and a rotor mill type mixer can also be used.
[0118] There is no restriction on the stirring method, and the usual stirring method of directly stirring the reaction solution in the reaction tank from the upper part, lower part, side part, etc. of the reaction tank can be adopted. In addition, a part of the reaction solution can be taken out of the reaction tank by piping, etc. and stirred by a pipeline stirrer, etc., so that the reaction solution is circulated. The type of stirring paddle can also be selected from known stirring paddles, specifically, a propeller, a propeller, a turbine paddle, a fan-shaped turbine paddle, a disc-shaped turbine paddle, a Pfaudler paddle, a full zone paddle, a Maxblend paddle, etc. can be cited.
[0119] The type of the polycondensation reaction tank used in the present invention is not particularly limited, and examples thereof include vertical stirring polymerization tank, horizontal stirring polymerization tank, thin film evaporation polymerization tank, etc. The polycondensation reaction tank may be one, or may be a plurality of tanks formed by connecting two or more tanks of the same or different types in series. In the late stage of polycondensation when the viscosity of the reaction solution rises, it is preferred to select a horizontal stirring polymerization machine with a thin film evaporation function that has excellent interface renewal, plug flow, and self-cleaning properties.
[0120] <Pelletization>
[0121] The polyester in a molten state at a high temperature obtained by the polycondensation reaction can be pelletized while being cooled to prepare polyester pellets.
[0122] The following methods are widely used for pelletizing: a strand cutting method in which the polyester in a high-temperature and molten state is extruded from the nozzle hole of a die head using a gear pump or an extruder, and the strands are cooled with water or the like and cut with a cutter at the same time, or the cooled and solidified strands are cut with a cutter; an underwater hot cutting method in which the polyester is extruded from the nozzle hole into water and immediately cut in a molten state; and the like.
[0123] In the aliphatic aromatic polyester of the present invention, the underwater hot cutting method is preferred because the obtained pellets have less debris, the obtained pellets have a low angle of repose, the pellets have good conveying stability, and the stability of feeding to the molding machine during molding is good. In the underwater cutting method, the lower limit of the cooling water temperature is preferably 10°C or more, more preferably 20°C or more, and the upper limit is preferably 70°C or less, more preferably 60°C or less, and further preferably 50°C or less.
[0124] The shapes of the pellets include spherical, ellipsoidal, cylindrical, elliptical, long cylindrical, quadrangular, cocoon-shaped, and flattened shapes. In the hot-cut method in water, the pellets are mostly ellipsoidal, cylindrical, elliptical, spherical, cocoon-shaped, and flattened shapes thereof, preferably ellipsoidal and cylindrical.
[0125] <Polyester Manufacturing Process>
[0126] In the production of the aliphatic aromatic polyester of the present invention, the raw material is usually mixed with an aliphatic diol component such as 1,4-butanediol in a raw material mixing tank, and supplied to the esterification reaction tank in the form of slurry or liquid through a raw material supply line. When a catalyst is added during the esterification reaction, a solution of an aliphatic diol component such as 1,4-butanediol is prepared in a catalyst preparation tank, and then the catalyst solution is supplied through a catalyst supply line.
[0127] The gas distilled from the esterification reaction tank is separated into a high boiling component and a low boiling component in a distillation column through a distillation line. Generally, the main components of the high boiling component are aliphatic diol components such as 1,4-butanediol, and the main components of the low boiling component are water and decomposition products of aliphatic diol components such as 1,4-butanediol.
[0128] The high-boiling components separated in the distillation tower are extracted from the extraction line, and a part of them are circulated to the esterification reaction tank through the recycling line through the pump, and a part of them are returned to the distillation tower through the circulation line. The remaining part is extracted to the outside through the extraction line. On the other hand, the light-boiling components separated in the distillation tower are extracted from the gas extraction line, condensed in the condenser, and temporarily stored in the tank through the condensate line. A part of the light-boiling components collected in the tank is returned to the distillation tower through the extraction line, the pump and the circulation line, and the remaining part is extracted to the outside of the system through the extraction line. The condenser is connected to the exhaust device through the exhaust line. The esterification reaction product generated in the esterification reaction tank is supplied to the polycondensation reaction tank (the first polycondensation reaction tank) through the extraction pump and the extraction line of the esterification reaction product.
[0129] <Physical Properties of Polyester>
[0130] The aliphatic aromatic polyester of the present invention obtained by the method for producing an aliphatic aromatic polyester of the present invention is produced so as to contain an appropriate amount of the nucleating agent relative to the polyester because a specific nucleating agent is present in the production process.
[0131] The lower limit of the intrinsic viscosity (IV) of the aliphatic aromatic polyester of the present invention is preferably 1.0 dL / g or more, particularly preferably 1.2 dL / g or more. The upper limit of the intrinsic viscosity of the aliphatic aromatic polyester of the present invention is preferably 2.5 dL / g, more preferably 2.2 dL / g, particularly preferably 2.0 dL / g. If the intrinsic viscosity is less than the lower limit, it is difficult to obtain sufficient mechanical strength when the molded product is made. If the intrinsic viscosity exceeds the upper limit, the melt viscosity is high during molding and it is difficult to mold. The intrinsic viscosity of the aliphatic aromatic polyester of the present invention is measured by the method described in the Examples section described later.
[0132] The terminal acid value of the aliphatic aromatic polyester of the present invention is preferably 30 eq. / ton or less, more preferably 20 eq. / ton or less, and further preferably 15 eq. / ton or less. If the terminal acid value of the aliphatic aromatic polyester exceeds the upper limit, the viscosity decrease due to hydrolysis becomes significant, and the quality may be significantly impaired. The terminal acid value of the aliphatic aromatic polyester of the present invention is measured by the method described in the Examples section described later.
[0133] The melting point (Tm) of the polyester of the present invention is 2) is not particularly limited, and the melting point of the aliphatic aromatic polyester satisfying the above-mentioned appropriate intrinsic viscosity and terminal acid value is usually about 100 to 150°C. Therefore, the melting point (Tm) of the nucleating agent used in the present invention is 1 ) is preferably about 100 to 165° C. The melting point of the aliphatic aromatic polyester of the present invention is measured by the method described in the Examples section below.
[0134] The cooling crystallization peak time of the aliphatic aromatic polyester of the present invention based on DSC is preferably 60 seconds or less, more preferably 50 seconds or less. If the cooling crystallization peak time is below the above upper limit, crystallization can be fully promoted and problems caused by insufficient crystallization can be suppressed. The lower limit of the cooling crystallization peak time is not particularly limited, but is generally about 30 seconds. The cooling crystallization peak time of the aliphatic aromatic polyester of the present invention is measured by the method described in the Examples section described later.
[0135] <Polyester composition>
[0136] The aliphatic aromatic polyester of the present invention obtained by the present invention can be mixed with aliphatic polyester, aliphatic hydroxycarboxylic acid polyester, etc. It can be further mixed with carbodiimide compounds, fillers, and plasticizers used as needed. In addition, other biodegradable resins (such as polycaprolactone, polyamide, polyvinyl alcohol, cellulose ester, etc.), starch, cellulose, paper, wood powder, chitosan·chitosan, coconut shell powder, walnut shell powder and other animal / plant material fine powders, or mixtures thereof can be mixed within the range that does not hinder the effect of the present invention. In addition, for the purpose of adjusting the physical properties and processability of the molded product, it can also contain heat stabilizers, plasticizers, lubricants, anti-blocking agents, nucleating agents other than the nucleating agent satisfying the above formula (1), inorganic fillers, colorants, pigments, ultraviolet absorbers, light stabilizers and other additives, modifiers, crosslinking agents, etc.
[0137] The method for producing the polyester composition from the aliphatic aromatic polyester of the present invention is not particularly limited, and examples thereof include: a method of melt-mixing the raw material crumbs of the blended polyester in the same extruder; a method of melting and mixing them in different extruders; a method of kneading and mixing using a common kneading machine such as a single-screw extruder, a twin-screw extruder, a Banbury mixer, an open rubber mixer, a Brabender plastometer, a kneading mixer, etc. In addition, the raw material crumbs can be directly supplied to a molding machine to prepare the composition and simultaneously obtain the molded product thereof.
[0138] Example
[0139] The present invention is described in more detail below by way of examples. As long as it does not exceed the gist thereof, the present invention is not subject to any limitation of the following examples.
[0140] The measurement methods of physical properties and evaluation items used in the following examples are as follows.
[0141] <Intrinsic viscosity (IV) (dL / g)>
[0142] The viscosity can be determined using an Ubbelohde viscometer as follows.
[0143] The effusion seconds of a polymer solution having a concentration of 0.5 g / dL and the effusion seconds of the solvent alone were measured at 30° C. using a mixed solvent of phenol / tetrachloroethane (mass ratio 1 / 1), and the intrinsic viscosity was determined from the following formula (2).
[0144] IV=((1+4K H η SP ) 0.5 -1) / (2K H C)…(2)
[0145] η SP =η / η0-1, η is the outflow time of the sample solution in seconds, η0 is the outflow time of the solvent in seconds, C is the concentration of the sample solution (g / dL), K H is the Huggins constant. K H Use 0.33.
[0146] <Terminal acid value of ester oligomer (eq. / ton)>
[0147] 0.3 g of the paste-like ester oligomer was taken into a 100 mL beaker, 40 mL of benzyl alcohol was added, and the mixture was heated on a hot plate at 180°C while blowing dry nitrogen. Dissolution was confirmed during the process, and after 20 minutes, the mixture was cooled to 60°C by water cooling. The oil droplets attached to the wall of the beaker were washed with 10 mL of benzyl alcohol, 1 to 2 drops of phenol red indicator were added to the solution, and the mixture was titrated with 0.1 mol / L potassium hydroxide methanol solution while blowing dry nitrogen, and the titration was terminated when the color changed from yellow to red. In addition, the same operation was performed using only benzyl alcohol as a blank, and the terminal acid value (terminal carboxyl group amount) was calculated by the following formula (3).
[0148] <Terminal acid value of polyester (eq. / ton)>
[0149] The pelletized polyester was dried at 60°C for 8 hours using a vacuum dryer, cooled to room temperature in a dryer, and 0.5 g of the obtained sample was accurately weighed and placed in a test tube. 25 mL of benzyl alcohol was added and dissolved at 195°C for 3 minutes while blowing dry nitrogen. Then, the mixture was cooled and stirred in an ice bath for 40 seconds, and then 2 mL of ethanol was slowly added. 1 to 2 drops of phenol red indicator were added to the solution, and titrated with 0.1 mol / L sodium hydroxide benzyl alcohol solution while blowing dry nitrogen and stirring. The titration was terminated when the color changed from yellow to red. In addition, as a blank, the same operation was performed without adding the polyester sample, and the terminal acid value (terminal carboxyl group amount) was calculated by the following formula (3).
[0150] <Calculation formula for terminal acid value>
[0151] Terminal acid value (eq. / ton) = (ab) × 0.1 × f / w…(3)
[0152] Here, a is the amount (μL) of 0.1 mol / L sodium hydroxide benzyl alcohol solution required for titration, b is the amount (μL) of 0.1 mol / L sodium hydroxide benzyl alcohol solution required for blank titration, w is the amount (g) of the ester oligomer or polyester sample, and f is the titration rate of 0.1 mol / L sodium hydroxide benzyl alcohol solution.
[0153] The titration rate (f) of a 0.1 mol / L sodium hydroxide benzyl alcohol solution was determined by the following method.
[0154] Take 5cm of methanol in the test tube 3 , add 1-2 drops of ethanol solution of phenol red as an indicator, and use 0.1 mol / L sodium hydroxide benzyl alcohol solution 0.4 cm 3 Titrate to the color change point, then use a 0.1 mol / L hydrochloric acid aqueous solution with a known titration rate as the standard solution, and add 0.2 cm 3 , and titrated again with 0.1 mol / L sodium hydroxide benzyl alcohol solution to the color change point (the above operation was carried out under blowing dry nitrogen). The titration rate (f) was calculated by the following formula (4).
[0155] Titration rate (f) = titration rate of 0.1 mol / L hydrochloric acid aqueous solution × amount of 0.1N hydrochloric acid aqueous solution taken (μL) / titration of 0.1 mol / L sodium hydroxide benzyl alcohol solution (μL)…(4)
[0156] <Melting point of polyester (℃)>
[0157] For Examples 1 to 3 and Comparative Example 1 described below, the endothermic peak temperature when the temperature was increased from room temperature to 250° C. at a rate of 20° C. / min was measured using DSC6220 (manufactured by SII Nanotechnology) and was taken as the melting point of the polyester.
[0158] For Examples 5 to 13 and Comparative Examples 2 to 5 described below, the endothermic peak temperature when the temperature was raised from room temperature to 250° C. at a rate of 20° C. / min was measured using DSC7020 (manufactured by Hitachi High-Tech Science Co., Ltd.), and this was taken as the melting point of the polyester.
[0159] <Melting Enthalpy Ratio of Polyester>
[0160] Use DSC7020 (manufactured by Hitachi High-Tech Science) to heat from room temperature to 200°C at a rate of 10°C / min, then cool from 200°C to -50°C at a rate of 10°C / min, and further heat from -50°C to 200°C at 10°C / min. For the resin obtained by removing the nucleating agent from the aliphatic aromatic polyester, when measuring DSC using the above method, the area of the endothermic peak corresponding to the melting of the sample resin during the second heating process is defined as the melting enthalpy (ΔHm and ΔHm0, respectively). At this time, the value obtained by dividing ΔHm by ΔHm0 (ΔHm / ΔHm0) is defined as the melting enthalpy ratio for evaluation. The value of (ΔHm / ΔHm0) is an indicator of the degree of promotion of crystallization. The larger the value, the more promoted the crystallization.
[0161] <Peak crystallization time of polyester at low temperature (seconds)>
[0162] 10±1 mg of polyester was placed in an aluminum open pan for DSC measurement, and heated and melted at 200°C for 10 minutes under a nitrogen atmosphere. The sample pan was placed in a DSC6220 (manufactured by SII Nanotechnology) while maintaining the molten state, and isothermal measurement was performed at 10°C. The time when the exotherm due to crystallization reached the maximum value was recorded, and the same measurement was performed at 20°C, 30°C, and 40°C. The shortest time to reach the exotherm maximum value was taken as the cooling crystallization peak time. The smaller the value, the more the crystallization was promoted.
[0163] [Preparation of polycondensation catalyst]
[0164] 343.5 parts by weight of magnesium acetate tetrahydrate were added to a reactor with a stirring device, and 1434 parts by weight of anhydrous ethanol (purity 99% by weight or more) were further added. 218.3 parts by weight of ethyl acid phosphate (the mixing weight ratio of monoester and diester was 45:55) was further added and stirred at 23°C. After confirming that the magnesium acetate was completely dissolved, 410.0 parts by weight of tetra-n-butyl titanate were added. Stirring was continued for further 10 minutes to obtain a uniform mixed solution. The mixed solution was controlled at a temperature below 60°C and concentrated under reduced pressure. About half of the ethanol added was distilled off, leaving a translucent viscous liquid. 1,4-butanediol 1108 parts by weight was added thereto, the temperature was controlled at a temperature below 80°C, and the mixture was further concentrated under reduced pressure to obtain a catalyst solution with a titanium atom content of 3.5% by weight.
[0165] [Example 1]
[0166] Into a reaction vessel equipped with a stirring device, a nitrogen inlet, a heating device, a thermometer and a pressure reducing port, 33.6 parts by weight of succinic acid, 38.6 parts by weight of terephthalic acid, 69.7 parts by weight of 1,4-butanediol, 0.138 parts by weight of trimethylolpropane, 0.10 parts by weight of polyethylene wax ("ACumist B6" manufactured by Honeywell, melting point: 124°C), 0.0017 parts by weight of sodium hydroxide (NaOH) as raw materials were added, and tetra-n-butyl titanate was further added in a manner of 30 ppm by weight in terms of titanium atoms relative to the obtained polyester. Nitrogen was introduced into the container while stirring the contents of the container, and the system was replaced by a nitrogen atmosphere by decompression. Next, the temperature was raised from 160°C to 230°C in 1 hour while stirring the system, and the reaction was carried out at this temperature for 3 hours. The terminal acid value of the obtained ester oligomer was measured and the result was 90 eq. / ton.
[0167] The catalyst solution was added to the ester oligomer in an amount of 70 ppm by weight in terms of titanium atoms relative to the obtained polyester, and the temperature was raised to 250° C. over 45 minutes, while the pressure was reduced to 0.07×10 3 Pa or less, and the polycondensation is continued while maintaining the heating and reduced pressure state. When the prescribed viscosity is reached, the polymerization is terminated to obtain a polyester copolymer.
[0168] The distillate from the esterification reaction and polycondensation reaction was recovered, and the tetrahydrofuran concentration was measured by the absolute calibration method of gas chromatography, and the by-product of tetrahydrofuran (THF by-product) was calculated to be 0.0047 parts by weight per 100 parts by weight of the polyester copolymer.
[0169] [Comparative Example 1]
[0170] A polyester copolymer was obtained in the same manner as in Example 1 except that polyethylene wax and sodium hydroxide were not added.
[0171] [Example 2]
[0172] A polyester copolymer was obtained in the same manner as in Example 1 except that the amount of polyethylene wax added was changed to 10 times that of Example 1.
[0173] [Example 3]
[0174] A polyester copolymer was obtained in the same manner as in Example 1 except that polypropylene wax ("PP7502" manufactured by Clariant Chemicals, melting point: 160° C.) was added instead of the polyethylene wax.
[0175] [Example 4]
[0176] A polyester copolymer was obtained in the same manner as in Example 1 except that the amount of sodium hydroxide added was changed to 10 times that in Example 1.
[0177] The melting points (Tm) of the polyester copolymers prepared in Examples 1 to 3 and Comparative Example 1 were 2 ) and the cooling crystallization peak time were measured, and the results are shown in Table 1 together with the manufacturing conditions.
[0178] In addition, the polymerization time in Examples 1 and 4 and Comparative Example 1, the intrinsic viscosity (IV) of the produced polyester copolymer, the polymerization rate obtained by dividing the intrinsic viscosity by the polymerization time, the terminal acid value of the produced polyester polymer, and the amount of THF by-product during the production were measured, and the results are shown in Table 2 together with the production conditions.
[0179] In Tables 1 and 2, polyethylene wax is referred to as "PE-Wax" and polypropylene wax is referred to as "PP-Wax". The melting point (Tm 1 ) and the melting point (Tm 2 ) difference (Tm 1 -Tm 2 ) is recorded as "ΔTm".
[0180] In Tables 1 and 2, the amount of the nucleating agent added is the amount added relative to the polyester copolymer, and the amount of the basic inorganic compound added is the amount added in terms of metal atoms relative to the polyester copolymer.
[0181] [Table 1]
[0182]
[0183] [Table 2]
[0184]
[0185] As can be seen from Table 1, the polyester copolymers of Examples 1 to 3 in which the nucleating agent satisfying formula (1) of the present invention is present in the reaction system have shorter cooling crystallization peak times than the polyester copolymer of Comparative Example 1 in which the nucleating agent is not present, thus promoting crystallization.
[0186] From the comparison between Examples 1 and 4 and Comparative Example 1 in Table 2, it can be seen that in Examples 1 and 4, the addition of NaOH can suppress (neutralize) the decomposition reaction based on the acid, and the by-product amount of THF and the terminal acid value can be reduced.
[0187] [Example 5]
[0188] Into a reaction vessel equipped with a stirring device, a nitrogen inlet, a heating device, a thermometer and a pressure reducing port, 24.2 parts by weight of succinic acid, 48.0 parts by weight of 2,5-furandicarboxylic acid, 92.4 parts by weight of 1,4-butanediol, 0.138 parts by weight of trimethylolpropane, 1.00 parts by weight of polyethylene wax ("ACumist B6" manufactured by Honeywell, melting point: 124°C) as raw materials were added, and tetra-n-butyl titanate was further added in a manner of 30 ppm by weight of titanium atoms relative to the obtained polyester. Nitrogen was introduced into the container while stirring the contents of the container, and the system was placed in a nitrogen atmosphere by decompression replacement. Next, the system was heated from 170°C to 190°C in 1 hour while stirring, and the reaction was carried out at this temperature for 1 to 2 hours. Then, tetra-n-butyl titanate was further added in an amount of 70 ppm by weight in terms of titanium atoms relative to the obtained polyester, and the temperature was raised to 240° C. over 1.5 hours, while the pressure was reduced to 0.07×10 3 Pa or less, and the polycondensation is continued while maintaining the heating and reduced pressure state. When the prescribed viscosity is reached, the polymerization is terminated to obtain a polyester copolymer.
[0189] [Comparative Example 2]
[0190] In Example 5, except that polyethylene wax was not added, the polyester copolymer was obtained in the same manner. The distillate from the esterification reaction and polycondensation reaction was recovered, and the tetrahydrofuran concentration was measured by gas chromatography. The by-product of tetrahydrofuran (THF by-product) was calculated and found to be 19.2 parts by weight per 100 parts by weight of the polyester copolymer.
[0191] [Example 6]
[0192] Into a reaction vessel equipped with a stirring device, a nitrogen inlet, a heating device, a thermometer and a pressure reducing port, 24.2 parts by weight of succinic acid, 48.0 parts by weight of 2,5-furandicarboxylic acid, 92.4 parts by weight of 1,4-butanediol, and 0.138 parts by weight of trimethylolpropane as raw materials are added, and tetra-n-butyl titanate is further added in an amount of 30 ppm by weight of titanium atoms relative to the obtained polyester. Nitrogen gas is introduced into the container while stirring the contents of the container, and the system is placed in a nitrogen atmosphere by decompression replacement. Next, while stirring the system, the temperature is raised from 170°C to 190°C in 1 hour, and the reaction is carried out at this temperature for 1 to 2 hours. Thereafter, tetra-n-butyl titanate is further added in an amount of 70 ppm by weight of titanium atoms relative to the obtained polyester, the temperature is raised to 240°C in 1.5 hours, and the pressure is reduced to 0.07×10 3 Pa or less, and the polycondensation reaction is carried out while heating and reducing pressure until the specified viscosity is reached. Next, 1.00 weight part of polyethylene wax ("Luwax AH3" manufactured by BASF, melting point: 113°C) is added to 100 weight parts of the above resin in a molten state, and the polymerization is terminated after kneading to obtain a polyester copolymer.
[0193] [Example 7]
[0194] In Example 6, a polyester copolymer was obtained in the same manner except that the polyethylene wax ("Luwax AH3" manufactured by BASF) was changed to a polyethylene wax ("ACumist A6" manufactured by Honeywell, melting point: 132°C).
[0195] [Example 8]
[0196] In Example 6, a polyester copolymer was obtained in the same manner except that the polyethylene wax ("Luwax AH3" manufactured by BASF) was changed to a fatty acid amide ("Slipacks H" manufactured by Mitsubishi Chemical Corporation, compound name: ethylene bis-12-hydroxystearamide, melting point: 145°C).
[0197] [Example 9]
[0198] In Example 6, a polyester copolymer was obtained in the same manner except that the polyethylene wax ("Luwax AH3" manufactured by BASF) was changed to a phosphoric acid ester metal salt ("Ecopromote" manufactured by Nissan Chemical Industries, Ltd., compound name: zinc phenylphosphonate, melting point: 164°C).
[0199] [Comparative Example 3]
[0200] In Example 6, a polyester copolymer was obtained in the same manner except that the polyethylene wax ("Luwax AH3" manufactured by BASF) was changed to talc ("NANO ACE D-600" manufactured by Nippon Talc Co., Ltd., melting point: 900°C or higher (decomposition)).
[0201] [Comparative Example 4]
[0202] In Example 6, a polyester copolymer was obtained in the same manner except that the polyethylene wax ("Luwax AH3" manufactured by BASF) was changed to talc ("MS-KY" manufactured by Nippon Talc Co., Ltd., melting point 900°C or higher (decomposed)).
[0203] [Example 10]
[0204] The polyester copolymer obtained in Example 5 was supplied to a twin-screw extruder (Parker Corporation, HK-25D (41D), barrel temperature: 220°C) equipped with an underwater cutter (ECON, EUP10, cooling water temperature: 14-28°C), melt-kneaded and then cut to produce pellets (long diameter of about 5 mm, short diameter of about 3 mm) having a spheroidal shape composed of an aliphatic aromatic polyester composition. The pellets immediately after cutting were cooled in cooling water at 15-30°C for several seconds and then centrifugally dehydrated for recovery.
[0205] [Example 11]
[0206] In Example 5, a polyester copolymer was obtained in the same manner except that the amount of polyethylene wax added was changed to 0.1 times (1000 ppm by weight). The obtained polyester copolymer was pelletized in the same manner as in Example 10. The pellets immediately after cutting were cooled in cooling water at 15 to 30° C. for several seconds and then centrifuged for dehydration and recovery.
[0207] In both of Examples 10 and 11, no significant fusion was observed in the pelletized pellets. In particular, when the cooling water temperature was lowered, a tendency of reduced fusion was observed.
[0208] [Example 12]
[0209] In Example 5, all the procedures were carried out in the same manner except that tetraethylammonium hydroxide (manufactured by Tokyo Chemical Industry Co., Ltd., Et4NOH) was added simultaneously with the raw materials so as to be 300 ppm by weight relative to the obtained polyester, thereby obtaining a polyester copolymer.
[0210] The distillate from the esterification reaction and the polycondensation reaction was recovered, and the tetrahydrofuran concentration was measured by gas chromatography. The by-product of tetrahydrofuran (THF by-product) was calculated and found to be 16.3 parts by weight per 100 parts by weight of the polyester copolymer.
[0211] [Example 13]
[0212] In Example 5, a polyester copolymer was produced in the same manner except that sodium hydroxide (manufactured by Tokyo Chemical Industry Co., Ltd., NaOH) was added simultaneously with the raw materials so as to be 30 ppm by weight in terms of sodium atoms relative to the obtained polyester.
[0213] The distillate from the esterification reaction and the polycondensation reaction was recovered, and the tetrahydrofuran concentration was measured by gas chromatography. The by-product of tetrahydrofuran (THF by-product) was calculated and found to be 17.0 parts by weight per 100 parts by weight of the polyester copolymer.
[0214] [Comparative Example 5]
[0215] A polyester copolymer not containing a nucleating agent was obtained in the same manner as in Comparative Example 2 except that 22.3 parts by weight of succinic acid, 52.2 parts by weight of dimethyl 2,5-furandicarboxylate, 68.1 parts by weight of 1,4-butanediol, and 0.138 parts by weight of trimethylolpropane were used as raw materials.
[0216] The distillate from the esterification reaction and the polycondensation reaction was recovered, and the tetrahydrofuran concentration was measured by gas chromatography. The by-product of tetrahydrofuran (THF by-product) was calculated and found to be 7.4 parts by weight per 100 parts by weight of the polyester copolymer.
[0217] The melting points (Tm) of the polyester copolymers prepared in Examples 5 to 11 and Comparative Examples 2 to 4 were 2 ) and melting enthalpy ratio (ΔHm / ΔHm0) were measured, and the results are shown in Tables 3A, 3B, and 4 together with the manufacturing conditions.
[0218] About Examples 10 and 11, the pellet shape and granulation property were evaluated, and the results are shown in Table 4 together.
[0219] In addition, the polymerization time in Examples 12 and 13 and Comparative Examples 2 and 5, the intrinsic viscosity (IV) of the produced polyester copolymer, the polymerization rate obtained by dividing the intrinsic viscosity by the polymerization time, the terminal acid value of the produced polyester copolymer, the amount of THF by-product during the production, the melting point (Tm 2 ) and melting enthalpy ratio (ΔHm / ΔHm0) were measured, and the results are shown in Table 5 together with the manufacturing conditions.
[0220] In Tables 3A, 3B, 4, and 5, polyethylene wax is described as “PE-Wax”, and the melting point (Tm) of the nucleating agent is described as 1 ) and the melting point (Tm 2 ) difference (Tm 1 -Tm 2 ) is recorded as "ΔTm".
[0221] The addition amounts of the nucleating agent and the basic organic compound in Tables 3A, 3B, 4 and 5 are the addition amounts relative to the polyester copolymer, and the addition amount of the basic inorganic compound is the addition amount in terms of metal atoms relative to the polyester copolymer.
[0222]
[0223] [Table 4]
[0224]
[0225] [Table 5]
[0226]
[0227] As can be seen from Tables 3A and 3B, the polyester copolymers of Examples 5 to 9 containing the nucleating agent satisfying Formula (1) of the present invention have larger values of ΔHm / ΔHm0 than the polyester copolymer of Comparative Example 2 containing no nucleating agent, and crystallization is promoted.
[0228] In Comparative Examples 3 and 4 using nucleating agents that do not satisfy the formula (1), the value of ΔHm / ΔHm0 is not sufficiently increased, and it is found that the effect of promoting crystallization is low.
[0229] As can be seen from Examples 10 and 11 in Table 4, there are some differences in the value of ΔHm / ΔHm0 depending on the amount of nucleating agent added that satisfies formula (1), but in either case, by granulating the aliphatic aromatic polyester of the present invention using an underwater cutter, ellipsoidal pellets that are less likely to fuse can be produced, and almost no adhesion is confirmed.
[0230] From the comparison between Examples 12 and 13 and Comparative Examples 2 and 5 in Table 5, it can be seen that even when a furan dicarboxylic acid component is used as a raw material, when a basic compound is added (Examples 12 and 13), the decomposition reaction based on the acid can be suppressed (neutralized) and the amount of THF by-product can be reduced.
[0231] Although the present invention has been described in detail using specific embodiments, it will be apparent to one skilled in the art that various modifications can be made without departing from the spirit and scope of the present invention.
[0232] This application is based on Japanese Patent Application No. 2020-021757 filed on February 12, 2020, the entire contents of which are incorporated herein by reference.
Claims
1. A method for producing an aliphatic aromatic polyester, characterized in that: When an aliphatic aromatic polyester is produced by subjecting an aliphatic diol component, an aliphatic dicarboxylic acid component and an aromatic dicarboxylic acid component as raw materials to an esterification and / or transesterification reaction and a polycondensation reaction in the presence of a catalyst, a nucleating agent satisfying the following formula (1) is allowed to exist in the reaction system: 0℃<Tm 1 -Tm 2 ≤50℃ ···(1) In the formula (1), Tm 1 is the melting point of the nucleating agent, in °C, Tm 2 is the melting point of aliphatic aromatic polyester, in °C, The molar ratio of the aliphatic dicarboxylic acid component to the aromatic dicarboxylic acid component is 50:50 to 60:
40. The aliphatic diol component is an alkylene glycol having 6 or less carbon atoms, The aliphatic dicarboxylic acid component is succinic acid, succinic anhydride, adipic acid, sebacic acid or their alkyl esters, The aromatic dicarboxylic acid component is a terephthalic acid component and / or a furan dicarboxylic acid component, The nucleating agent is a hydrocarbon nucleating agent, an aliphatic amide nucleating agent or a phosphate metal salt nucleating agent.
2. A method for producing an aliphatic aromatic polyester, characterized in that: When an aliphatic aromatic polyester is produced by subjecting an aliphatic diol component, an aliphatic dicarboxylic acid component and an aromatic dicarboxylic acid component as raw materials to an esterification and / or transesterification reaction and a polycondensation reaction in the presence of a catalyst, a nucleating agent satisfying the following formula (1) is allowed to exist in the reaction system: 0℃<Tm 1 -Tm 2 ≤50℃ ···(1) In the formula (1), Tm 1 is the melting point of the nucleating agent, in °C, Tm 2 is the melting point of aliphatic aromatic polyester, in °C, The aromatic dicarboxylic acid component is a furan dicarboxylic acid component, The aliphatic diol component is an alkylene glycol having 6 or less carbon atoms, The aliphatic dicarboxylic acid component is succinic acid, succinic anhydride, adipic acid, sebacic acid or their alkyl esters, The nucleating agent is a hydrocarbon nucleating agent, an aliphatic amide nucleating agent or a phosphate metal salt nucleating agent.
3. The method for producing an aliphatic aromatic polyester according to claim 1 or 2, wherein: The nucleating agent is present in an amount of 100 ppm by weight to 10,000 ppm by weight based on the produced aliphatic aromatic polyester.
4. The method for producing aliphatic aromatic polyester according to claim 2, wherein: The molar ratio of the aliphatic dicarboxylic acid component to the aromatic dicarboxylic acid component is 40:60 to 60:
40.
5. The method for producing an aliphatic aromatic polyester according to claim 1 or 2, wherein: The esterification and / or transesterification reaction is carried out in the presence of a basic inorganic compound.
6. The method for producing aliphatic aromatic polyester according to claim 5, wherein: The basic inorganic compound is present in an amount of 1 ppm by weight to 100 ppm by weight in terms of metal atoms relative to the generated aliphatic aromatic polyester.
7. The method for producing an aliphatic aromatic polyester according to claim 1 or 2, wherein: The aliphatic dicarboxylic acid component is a succinic acid component.
8. The method for producing an aliphatic aromatic polyester according to claim 1 or 2, wherein: The aliphatic dicarboxylic acid component is a component derived from biomass.
9. The method for producing an aliphatic aromatic polyester according to claim 1 or 2, wherein: The aliphatic diol component is a component derived from biomass.
Citation Information
Patent Citations
Aliphatic-aromatic polyester and resin composition
JP2008031457A
Printed wiring board with electromagnetic wave shield sheet
JP2020021757A
High-strength copolyester and preparation method thereof
CN103804855A
Polyester resin
JP2008222737A
Heat-bondable polyester filament
JP2008266809A